Design and Analysis of a Prediction Model for Crop Yield Production in Agriculture (International Journal of Innovative Research in Computer Science & Technology, 2020)
Big Data Analytics has its importance in  almost all the real time applications ranging from Science  & Technology to Market Prediction to Weather  forecasting and many more. One such important area  where analytics played a crucial role is Agriculture.  Understanding the previously available agricultural data  and studying the underlying pattern can help in making  accurate future predictions. A well-known fact that the  majority of population (≥55%) in India is into  agriculture, the analytics and prediction can be really  useful to them. Various factors are to be considered which  have direct impact on the production of the crops. The use  of technology in agriculture has increased in recent year  and data analytics is one such trend that has penetrated  into the agriculture field. In this paper, the data of Government Crop Production is analyzed on various parameters which will help in predicting the Crop Yield.
Keywords: Big Data; Data Mining; Data Analytics; Agriculture; Prediction Model; Crop Prediction; Crop Yield